THE IMPACT OF DIGITAL COGNITIVE REHABILITATION TOOLS ON THE SOCIAL INTEGRATION OF PEOPLE WITH BRAIN INJURIES - Miszela Kałachurska,; Martyna Rożek,; Constancia Esther Guy,; Maria Nowakowska,; Aleksandra Lisowska,; Bartosz Nowak,; Oliwia Jerzyńska,; Maria Sierant,; Aleksandra Kowalewska-Kurek,; Mateusz Gural, (International Journal of Innovative Technologies in Social Science, 2026)
Traumatic brain injury (TBI) is a major global health concern, frequently resulting in persistent cognitive impairments that limit social integration and quality of life. Social integration—defined as meaningful participation in interpersonal relationships, employment, and community life—is strongly influenced by deficits in memory, attention, executive functioning, and social cognition. While traditional cognitive rehabilitation has demonstrated clinical benefits, its accessibility and long-term sustainability are often constrained by cost, resource demands, and reliance on in-person delivery. In recent years, digital cognitive rehabilitation tools, including mobile applications, virtual reality (VR), and tele-rehabilitation platforms, have emerged as promising alternatives that enable scalable, adaptive, and home-based interventions.This narrative review synthesizes current evidence on the impact of digital cognitive rehabilitation on social integration following TBI, with attention to clinical outcomes, socio-economic implications, and technological barriers. Findings suggest that digital interventions are effective in improving core cognitive domains and may indirectly enhance social functioning by supporting communication, self-efficacy, motivation, and participation in daily activities. VR-based approaches, in particular, offer ecologically valid environments that facilitate the transfer of cognitive gains to real-world social contexts. Economic evidence indicates that digital rehabilitation is often cost-effective or cost-saving, reducing healthcare system burden and supporting return-to-work outcomes.However, direct evidence linking digital cognitive rehabilitation to measurable social integration outcomes remains limited, and significant barriers persist related to digital access, usability, literacy, and ethical considerations. Future research should prioritize participation-level outcomes, long-term follow-up, and inclusive implementation strategies to maximize the social and societal benefits of digital rehabilitation after brain injury.